Месца беларускай мовы ў сучаснай Беларусі - Bandarovich, Veranika (Przegląd Środkowo-Wschodni, 2023)
The purpose of the study was to find out how much the Belarusian language is in demand among modern youth, namely, those who have chosen a non-philological profile of education, in order to predict the future fate of the Belarusian language. It turned out that the Belarusian youth in the majority speaks the title language of the nation at an average level. The level of teaching the Belarusian language in general education institutions was also assessed by the respondents mainly as average. For most young people, the Belarusian language is an attribute of a separate people and a value that needs to be protected. Responsibility for expanding the use of the Belarusian language is assumed by young people.